Audit Outcomes and Financial Health of Municipalities in South Africa - Shozi, Rejoyce (Graduate School of Business (GSB), 2024)
The regressing financial health, unfavourable annual audit outcomes, severed reputation for service delivery failures and resultant protests of South Africa's municipalities have raised a public furore. Several multi-stakeholder interventions purporting to address the financial mismanagement, audit regression and service delivery backlogs have been initiated by both the provincial and national governments. The intended impact and goal of these support interventions are yet to be realised. The objectives of this study were to examine the root causes that have cumulatively culminated in the deterioration of the financial health of the municipalities and investigate the relationship between financial conditions and audit outcomes not only in dysfunctional municipalities but also by studying the effect on all 257 municipalities in South Africa using data sourced from the 2016–2017, 2017–2018, 2018–2019 and 2019–2020 annual financial statements and reports from the Auditor-General of South Africa. In the first stage, descriptive statistics employed the median values of the variables: cash solvency, budget solvency, long-term solvency, service-level solvency and the financial condition index. The ordinary least squares estimation technique was employed to examine the relationship between financial health and audit outcomes using cross-sectional data from 257 municipalities sourced from the 2018–2019 financial year. The findings from the regression analysis indicated that no relationship exists between financial performance and the audit outcomes of financially distressed municipalities. The recommendations include eliminating political deployees assigned for administrative and technical appointments to allow for a clear separation between political representatives and competent, skilled and professional officials executing their roles and responsibilities objectively in a municipality. Further studies can improve existing literature by extensively examining the relationship between regressing financial performance, audit outcomes in dysfunctional and distressed municipalities and the role played by the political and administrative leadership.